A Cross-Sectional Network Analysis Study Applied to the Depression Anxiety Stress Scale-21 (DASS-21): A New Factor Revealed - Marco Antônio Silva Alvarenga; Amira Mohammed Ali; Carollina Souza Guilhermino; Tiago Geraldo de Azevedo; Kelly Fernandes Olímpio; Camila Kersul; Glacithane Lins da Cunha; Juliana Alvares-Teodoro; Pricila Cristina Correa Ribeiro; Marcela Mansur-Alves; Maycoln Lêoni Martins Teodoro; Paulo Felipe Ribeiro Bandeira (Mental Illness)
Conclusion: The classic structure of the DASS-21 (three factors) was replicated, but a four-factor model proved to be the one with the best statistical indices for nonclinical sample, providing new insight into the internal structure of this scale. In addition, there was factorial invariance between the groups compared. Implications for the use of the new structure are discussed.